Resilience of Child Victims of Sexual Violence with PTSD: The Role of Integrated Service Units for Women and Children Protection in Kendari City - Hasyim Abdillah; Lutfiana Nur Azizah; Ghery Safitra Fahrun; Rosdiana; Arni Nur Laila (Universitas Islam Negeri Madura, 2026)
This study investigated the resilience of child victims of sexual violence who developed Post-Traumatic Stress Disorder (PTSD) and analyzed the role of the Integrated Service Units for Women and Children Protection (UPT PPA) in Kendari City in facilitating their recovery. Adopting a qualitative case study methodology, the research utilized in-depth interviews and field observations with 10 child victims, aged 8 to 16 years, and 5 institutional staff members selected through purposive sampling based on victim status and psychological trauma indicators. The findings revealed that resilience in these children was shaped by an interplay of internal factors, such as self-efficacy and emotional regulation, and external factors, including family support and the multifaceted psychosocial interventions provided by UPT PPA. These interventions, which incorporated cultural, spiritual, and social support mechanisms, proved effective in strengthening the children's recovery processes. Ultimately, the results underscore the necessity of a holistic approach involving family, community, and institutional support in fostering resilience, while providing a basis for enhancing existing intervention models for child trauma survivors.